1990
DOI: 10.4319/lo.1990.35.5.1101
|View full text |Cite
|
Sign up to set email alerts
|

In situ filtering rates of Cladocera: Effect of body length, temperature, and food concentration

Abstract: The individual filtering rates of the cladocerans in Creteil Lake were measured in the daytime with 14C-labeled ChZorella during a seasonal survey. This mesotrophic, shallow, polymictic lake is characterized by small algae (~25 wrn) and cladocerans (< 1.3 mm). Multiple regression models were established for each genus and for all the cladocerans. Body length alone explained from 44 to 57% of the total variance in the filtering rates of Daphnia spp., Ceriodaphnia spp., and Diaphanosoma brachyurum. An additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
5

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 30 publications
1
49
1
5
Order By: Relevance
“…In general, larger zooplankton are more efficient feeders than smaller ones (Hall et al, 1976;Mourelatos & Lacroix, 1990). Therefore, rotifers could be outcompeted by the larger crustaceans.…”
Section: Dominant Species Groups and Variation In Species Compositionmentioning
confidence: 99%
“…In general, larger zooplankton are more efficient feeders than smaller ones (Hall et al, 1976;Mourelatos & Lacroix, 1990). Therefore, rotifers could be outcompeted by the larger crustaceans.…”
Section: Dominant Species Groups and Variation In Species Compositionmentioning
confidence: 99%
“…In freshwater ecosystems, herbivorous zooplankton grazing plays an important functional role by controlling algal blooms and transferring energy and matter upwards through the food chain [18]. Body size of zooplankton has been repeatedly suggested to play a key role in topdown control of algae [19,20], and this trait was found to be evolutionarily labile in cladoceran zooplankton (see electronic supplementary material for details). The importance of body size for top-down control is generally attributed to grazing efficiency asymmetry (selection effect), where larger species are superior grazers (figure 1a) [19,21] and therefore increasing community average size (CAS) might enhance grazing rates (GRs; figure 1c) [22].…”
Section: Introductionmentioning
confidence: 99%
“…Body size of zooplankton has been repeatedly suggested to play a key role in topdown control of algae [19,20], and this trait was found to be evolutionarily labile in cladoceran zooplankton (see electronic supplementary material for details). The importance of body size for top-down control is generally attributed to grazing efficiency asymmetry (selection effect), where larger species are superior grazers (figure 1a) [19,21] and therefore increasing community average size (CAS) might enhance grazing rates (GRs; figure 1c) [22]. Alternatively, it has been suggested that feeding niche partitioning (complementarity) between large and small zooplankton species may (co)determine top-down control on phytoplankton (figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…brachyurum, auxquelles il a été fourni une alimentation naturelle similaire en qualité et en quantité (dominance des Cyclotellà). Connaissant la tempé-rature et la taille des femelles, leur taux de filtration peut être estimé à partir des formules de Mourelatos et Lacroix (1990) et Mourelatos et al (1992). Dans l'intervalle de température 20 à 25°C, ce taux varie de 18 à 30 mL par individu et par jour pour des Ceriodaphnia de 1 mm et de 20 à 40 ou de 40 à 80 mL (selon l'équation utilis.ee) pour des Daphnies de 2 mm, alors qu'il ne varie que de 4 à 8,8 mL pour des Diaphanosoma.…”
Section: Discussion Et Conclusionunclassified